2009
DOI: 10.1143/jjap.48.07gm05
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonic Cleaning Equipment Using Waveguide Mode

Abstract: The clarity of the trace testifies to the accuracy and stability of the apparatus. A test was also carried out on a non-inductive circuit carrying alternating current. With a supply voltage of 250 V. r.m.s. it was found that current interception could be secured at a current peak up to 300 mA. There was no difficulty in maintaining a steady break at a zero of current up to a r.m.s. current of I A. A discussion upon contact material, suppression of the arc, etc. will be found in referenceb) in the bibliography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, an increase in the standing wave component induced by reflected waves from the waveguide end was observed only around the waveguide end. 6) Therefore, if we adopt measures to absorb the reflected waves, bubble collapse in the meniscus of the cleaning solution would be suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an increase in the standing wave component induced by reflected waves from the waveguide end was observed only around the waveguide end. 6) Therefore, if we adopt measures to absorb the reflected waves, bubble collapse in the meniscus of the cleaning solution would be suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…We previously proposed waveguide-type ultrasonic cleaning equipment that uses a quartz glass tube as the ultrasonic irradiator. 4,5) We estimated the acoustic amplitude irradiated from the waveguide side to be over 100 kPa, and we showed that the vibration velocity distribution of the waveguide side had a traveling wave distribution. 6) In a traveling ultrasonic wave field, bubbles receive radiation force in the traveling direction, and this force is expected to prevent the collapse of bubbles trapped at pressure antinodes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The sound source has the same configuration as the conventional Spot Shower. 10) In the Megatube, ultrasound supply point can be located anywhere within the cleaning equipment as the ultrasonic wave is directed through a thin quartz glass tube acting as a waveguide. Thus, it is possible to supply ultrasonic waves at a distance from the ultrasonic generator.…”
Section: Introductionmentioning
confidence: 99%
“…When ultrasound is irradiated onto liquid, physical and chemical effects occur due to vibration, cavitation, and streaming. These characteristics of ultrasound are applied to cleaning, [1][2][3] homogenization, atomization 4) and chemical reactions. 5,6) Recently, Li et al 7) have reported that the enzymatic hydrolysis of cellulose is enhanced by ultrasonic irradiation.…”
mentioning
confidence: 99%